A Politico-Economic Model of Aging, Technology Adoption and Growth - Francesco Lancia; Giovanni Prarolo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
Over the past century, all OECD countries have been characterized by a dramatic increase in economic conditions, life expectancy and edu- cational attainment. This paper provides a positive theory that explains how an economy might evolve when the longevity of its citizens both influences and is influenced by the process of economic development. We propose a three periods OLG model where agents, during their lifetime, cover dierent economic roles characterized by dierent incentive schemes and time horizon. Agents' decisions embrace two dimensions: the private choice about education and the public one upon innovation policy. The theory focuses on the crucial role played by heterogeneous interests in determining innovation policies, which are one of the keys to the growth process: the economy can be discontinuously innovation-oriented due to the dierent incentives of individuals and dierent schemes of political aggregation of preferences. The model produces multiple development regimes associated with dierent predictions about life expectancy evolu- tion, educational investment dynamics, and technology adoption policies. Transitions between these regimes depend on initial conditions and parameter values.
Keywords: 330; Sterblichkeit; Humankapital; Alternde Bevölkerung; Overlapping Generations; Technologiepolitik; Theorie; OECD-Staaten